2012
DOI: 10.3892/mmr.2012.1226
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance protein 2 genetic polymorphism and colorectal cancer recurrence in patients receiving adjuvant FOLFOX-4 chemotherapy

Abstract: Multidrug resistance protein 2 (MRP2), encoded by the ATP-binding cassette C2 (ABCC2) gene, is an efflux pump located on the apical membrane of many polarized cells, which transports conjugate compounds by an ATP-dependent mechanism. The correlation of G1249A ABCC2 polymorphism with the development of colorectal cancer (CRC) and poor prognosis was evaluated in patients who were treated with fluorouracil/-leucovorin (FL) plus oxaliplatin (FOLFOX-4). A total of 50 paraffin‑embedded tissue samples collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…CRC responds poorly to chemotherapy owing to multidrug resistance, which contributes to poor treatment outcomes of CRC with chemotherapeutic drugs (7). However, a recent study demonstrated a close correlation between LIMD1 expression in CRCs (8).…”
Section: Discussionmentioning
confidence: 99%
“…CRC responds poorly to chemotherapy owing to multidrug resistance, which contributes to poor treatment outcomes of CRC with chemotherapeutic drugs (7). However, a recent study demonstrated a close correlation between LIMD1 expression in CRCs (8).…”
Section: Discussionmentioning
confidence: 99%
“…1 However, recurrence following radical surgery is the leading factor to imply poor prognosis. 2 Although adjuvant chemotherapy can benefit patients with stage III disease, its role in patients with stage II CRC remains controversial due to the lack of data showing a definite benefit of chemotherapy in this group of patients as a whole. It is crucial to identify reliable predictive biomarkers that can guide personalized chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, as far as we are aware, there have been no studies to date directly addressing whether oxaliplatin or platinum derived from oxaliplatin is transported by MRP2. Recent reports of positive clinical-association studies linking ABCC2 genotype and MRP2 expression level with patient responses to oxaliplatin [ 26 , 27 ], and of MRP2 determining oxaliplatin antitumor responses and resistance in preclinical models [ 28 – 30 ], have added further to the urgency for fundamental understanding of this transport mechanism.…”
Section: Introductionmentioning
confidence: 99%